Presenting symptoms of COVID‐19 and clinical outcomes in hospitalised older adults. Issue 6 (21st June 2021) - Gregorevic, Kate; Maier, Andrea; Miranda, Roeisa; Loveland, Paula; Miller, Katherine; Buising, Kirsty; Marshall, Caroline; O'Gorman, Bronwyn; Tan, Amanda; Staggard, Kylie; O'Halloran, Tessa; Nguyen, Huong Xuan Thi; et al.
Abstract: Background: In July 2020, a COVID‐19 outbreak was recognised in the geriatric wards at a subacute campus of the Royal Melbourne Hospital affecting patients and staff. Patients were also admitted to this site after diagnosis in residential care. Aims: To describe the early symptoms and the outcomes of COVID‐19 in older adults. Methods: Patients diagnosed with COVID‐19 at the facility in July or August 2020 were identified and their medical records were examined to identify symptoms present before and after their diagnosis and to determine their outcomes. Results: Overall, 106 patients were identified as having COVID‐19, with median age of 84.3 years (range 41–104 years); 64 were diagnosed as hospital inpatients after a median length of stay of 49 days, 31 were transferred from residential aged care facilities with a known diagnosis and 11 were diagnosed after discharge. There were 95 patients included in an analysis of symptom type and timing onset. Overall, 61 (64.2%) were asymptomatic at the time of diagnosis of COVID‐19, having been diagnosed through screening initiated on site. Of these, 88.6% developed symptoms of COVID‐19 within 14 days. The most common initial symptom type was respiratory, but there was wide variation in presentation, including fever, gastrointestinal and neurological symptoms, many initially not recognised as being due to COVID‐19. Of 104 patients, 32 died within 30 days of diagnosis. Conclusions: COVID‐19 diagnosis is challenging due to the variance in symptoms. In the context of an outbreak, asymptomatic screening can identify affected patients early in the disease course.